2022
DOI: 10.1155/2022/5554290
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol Attenuates Metabolic Syndrome-Associated Heart Failure through Enhanced Mitochondrial Fusion

Abstract: Objectives. Transition from cardiac hypertrophy to failure involves adverse metabolic reprogramming involving mitochondrial dysfunction. We have earlier shown that vitamin D deficiency induces heart failure, at least in part, through insulin resistance. However, whether activation of vitamin D receptor (VDR) can attenuate heart failure and underlying metabolic phenotype requires investigation. Thus, we aimed to assess the cardioprotective potential of paricalcitol, a vitamin D receptor-activator, against cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…As mentioned, protein-bound uremic toxins such as indoxyl sulfate might hamper mitochondrial ATP generation, counteracting the protective effect of irisin in several aspects. Patients with CKD have several risk factors that dysregulate the PGC-1α–FNDC5 axis, such as vitamin D deficiency and the accumulation of protein-bound uremic toxins ( 60 , 61 ). An in vitro study demonstrated that indoxyl sulfate dysregulated the expression of PPARγ in C2C12 cells and therefore increased autophagy levels ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, protein-bound uremic toxins such as indoxyl sulfate might hamper mitochondrial ATP generation, counteracting the protective effect of irisin in several aspects. Patients with CKD have several risk factors that dysregulate the PGC-1α–FNDC5 axis, such as vitamin D deficiency and the accumulation of protein-bound uremic toxins ( 60 , 61 ). An in vitro study demonstrated that indoxyl sulfate dysregulated the expression of PPARγ in C2C12 cells and therefore increased autophagy levels ( 62 ).…”
Section: Discussionmentioning
confidence: 99%